The short-term effects of progressive vs conventional core stability exercise in rehabilitation of nonspecific chronic low back pain - Ebby Waqqash Mohamad Chan,; Ali Md Nadzalan,; Zainal Othman,; Eliza Hafiz,; Mohamad Shariff A. Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Core stability exercise programs are considered as a fundamental physical therapy treatment for chronic low back pain (LBP). However, it is still unclear which core stability program (progressive vs. conventional) is the most effective. A randomized controlled trial (RCT) was conducted to compare two core stability strategy strategies; progressive dynamic muscular stabilization technique (DMST) and conventional McGill Big 3 (MB3) in the rehabilitation of nonspecific chronic LBP. Thirty males diagnosed with nonspecific chronic LBP patients aged 33.57 ± 5.28 years were recruited and randomly assigned to; DMST and MGB3. All patients received additional conventional pain management treatment. The outcome measures were pain severity (motion, standing, sitting), functional disability, trunk endurance, lumbopelvic control, and body balance. All patients were assessed at baseline, 3rd week, and 6th week. A mixed design ANOVA showed both DMST and MGB3 improves all outcomes (p ≤ 0.05) specifically the pain severity and functional disability (p < 0.001, ηp2 = 0.81), trunk endurance (p < 0.001, ηp2 = 0.30), lumbopelvic control (p < 0.001, ηp2 = 0.242), and body balance (p = 0.003, ηp2 = 0.46) compared to baseline. However, no significant difference was found in all of the outcomes when comparing DMST and MBG3 (p > 0.05). In conclusion, both progressive DMST and conventional MGB3 core stability exercise programs are effective for nonspecific chronic LBP rehabilitation.